Impact of Self Help Groups’Trainings on Empowerment of Rural Women of Udaipur District - Jain, Simple (Indian Journal of Extension Education, 2017)
Training and Development function plays a significant role in energizing and empowering human resources by increasing  their skills through innovative and productive programmes. Women self-help groups are at present playing a vital role in  the personality and skill development of women in India. The Institute of Local Self Government and Responsible  Citizenship (ILSGRC),Vidya Bhawan Society, Udaipur has been conducting a two-day training program for SHG  members for better functioning of SHGs at the local level. The training covered the information about SHGs, bank  linkages, grading, government schemes and laws, health issues, participation in political process through Gram Sabha and  Ward Sabha etc. The Institute has organized trainings for SHGs for the past six years but to date, impact of training was not  assessed. Therefore, the present study was undertaken to study the effectiveness of training programmes. The present  study was conducted in 2 Blocks namely Badgoan and Gogunda of the Udaipur District. Atotal eight SHGs were selected  from 8 villages for the study. The sample consisted of 80 rural women SHG members. The results of the study demonstrate  that women gained knowledge about proper functioning of SHGs, initiation of micro enterprises and laws and schemes of  the women. The findings further show that their access was increased to the local level institutions like Anganwadi,  Panchayat, schools, post office etc. which enhanced their access to health and education. Women had more decision  making power in their household due to their SHG group and training. Thus the SHG training had been effective in  empowering the SHG members.
Keywords: Self Help Group; Training; knowledge; empowerment